2017
DOI: 10.1038/ncomms14165
|View full text |Cite
|
Sign up to set email alerts
|

Selective gating to vibrational modes through resonant X-ray scattering

Abstract: The dynamics of fragmentation and vibration of molecular systems with a large number of coupled degrees of freedom are key aspects for understanding chemical reactivity and properties. Here we present a resonant inelastic X-ray scattering (RIXS) study to show how it is possible to break down such a complex multidimensional problem into elementary components. Local multimode nuclear wave packets created by X-ray excitation to different core-excited potential energy surfaces (PESs) will act as spatial gates to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 31 publications
1
81
0
Order By: Relevance
“…1(b)). Computational details can be found in our previous RIXS study of the vibrationally cold water molecule [15] which confirms the applicability of the model. The normal mode picture describes well with respect to its minimum.…”
Section: Theorymentioning
confidence: 56%
See 4 more Smart Citations
“…1(b)). Computational details can be found in our previous RIXS study of the vibrationally cold water molecule [15] which confirms the applicability of the model. The normal mode picture describes well with respect to its minimum.…”
Section: Theorymentioning
confidence: 56%
“…In the ground electronic state, the two stretching modes are nearly degenerate and strongly coupled via Darling-Dennison coupling [23][24][25], which have to be considered together for a proper system description. In contrast, the bending mode is only weakly coupled to the stretching modes, and can thus be considered separately in an orthonormal approximation [15]. Previous studies [15,26] have shown that the bending mode is only weakly excited in XAS and RIXS near the two lowest core-excited states.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations